KOMBINASI RSS DAN SBR DALAM TEKNOLOGI PEMBUATAN KARET BANTALAN KAKI UNTUK MEBEL - Syamsul Bahri; Aprillena Tornadez Bondan (Balai Riset dan Standardisasi Industri Palembang, 2018)
This research was aimed to formulate the rubber step for furniture that meet its technical specification which approach to SNI 06-7032-2004 for Rubber Step of Motor Vehicle . This research used Ribbed Smokes Sheet (RSS) as natural rubber, combined with Styrene Butadiene Rubber (SBR) as synthetic rubber. The formulation of rubber compound used 100, 70, 50 and 30 phr of RSS, and 0, 30, 50 and 70 phr of SBR. The observed parameters for compounds were hardness (ASTM D 2240), tensile strength(ASTM D 412), elongation at break (ASTM D 412), modulus 310% (ASTM D 412), tear resistance (ASTM D 624), abrasion (ASTM D 298), and compression set 25%. The result showed that the best compound was formula III (contained 50 phr of RSS and 50 phr of SBR) with the test result for hardness was 68 Shore A, tensile strength 120 kg/cm2, elongation at break 355 %, modulus 100% was 25 kg/cm2, tear resistance 33kg/cm2, abrasion resistance 2,4 mm3/kgm, and compression set 25% value was 23%. Keywords : rubber step, RSS, SBR, furniture